Graphene electrode super capacitor and method to manufacture thereof - Mohd Asyadi ‘Azam, Mohd Abid; Raja Izamshah, Raja Abdullah (2014)
A graphene electrode super capacitor is provided. The graphene electrode super capacitor includes a carbon nanotube, a separator which is disposed between an anode and a cathode to separate said anode and said cathode from one another, and an electrolyte, contacting the anode and the cathode. The super capacitor having the carbon nanotube has a multi-walled carbon nanotube (MWCNT). In one embodiment, the carbon nanotube may be a single walled carbon nanotube (SWCNT). The separator may be a polypropylene (PP) separator with a pore size in the range 20mm to 25mm. The electrolyte may be made of an aqueous electrolyte and a non-aqueous electrolyte. The aqueous electrolyte may be used are sulphuric acid and potassium hydroxide electrolytes.